Radiation Oncology in the 21st Century: Prospective Randomized Trials That Changed Practice… or Didn’t! - Zakeri, Kaveh; Coleman, C. Norman; Vikram, Bhadrasain (Frontiers in Oncology, 2018)
In a two-part article published in 2009, we discussed the limitations of conventional radiation therapy, the challenges of studying new technologies in radiation oncology, and summarized the state-of-the science for various malignancies [1,2]. Here we summarize some of the most important prospective, randomized trials that during the intervening years have attempted to improve the tumor control and/or decrease the adverse effects of radiation therapy. For consistency, we have focused here on the null and alternate hypotheses as articulated by the investigators at the onset of each trial, since the outcome of the investigational treatment should be considered clinically significant only if the null hypothesis was rejected. The readers (and patients) are of course free to make their own judgments about the clinical significance of the results when the null hypothesis was not rejected.